Identificação de alterações genéticas ao diagnóstico e correlação com características clínicas e laboratoriais e evolução em pacientes com leucemia mielóide aguda - Ana Flavia Leonardi Tiburcio (2014)
The prevalence, the prognostic effect, and interaction with other molecular markers of DNMT3A mutations were studied in 415 adults patients with acute myeloid leukemia (AML) younger than 60 years, regarding its prognostic value. We showed mutations in DNMT3A in 96 of 415 patients with newly diagnosed AML (23.1%). Univariate Cox regression analysis showed that patients with DNMT3Amut AML show significantly worse overall survival (OS; P = 0.022; hazard ratio [HR] = 1.38; 95% confidence interval [CI], 1.04-1.81), and relapse-free survival (RFS; P = 0.005; HR = 1.52; 95% CI, 1.13-2.05) than DNMT3Awild-type AMLs. In a multivariable analysis, DNMT3A mutations express independent unfavorable prognostic value for OS (P = 0.003; HR = 1.82; 95% CI, 1.2-2.7) and RFS (P < 0.001; HR = 2.2; 95% CI, 1.4-3.3). In a composite genotypic subset of cytogenetic intermediate-risk AML without FLT3-ITD and NPM1 mutations, this association is particularly evident (OS: P = 0.013; HR = 2.09; 95% CI, 1.16-3.77; RFS: P = 0.001; HR = 2.65; 95% CI, 1.48-4.89). The effect of DNMT3A mutations in human AML remains elusive, because DNMT3Amut AMLs did not express a methylation or gene expression signature that discriminates them from patients with DNMT3Awild-type AML. We conclude that DNMT3A mutation status is an important factor to consider for risk stratification of patients with AML. Blood. 2012;119 (24):5824-5831